The Characteristics of Trans Metro Deli Bus Passengers in Medan - Fitri, Fadilla; Hasibuan, Gina Cynthia Raphita; Anas, M. Ridwan (Universitas Ibn Khaldun Bogor, 2025)
As the government’s response to the areas in developing countries, they took steps to reform the existing public transportation service system, one of which is by implementing the Trans Metro Deli (TMD) bus system, a revolutionary public transportation system. Intended to improve mobility and reduce congestion, TMD has become a symbol of transformation in urban transportation in Medan. TMD strives to provide reliable, affordable, and efficient public transportation services for Medan residents. The purpose of this study is to analyze the existing conditions of Trans Metro Deli buses and the characteristics of passengers by using questionnaires and descriptive analysis. The research results show that the existing conditions based on the Minimum Service Standards (Standar Pelayanan Minimal PM 27 Tahun 2015) regarding security, safety, and comfort are respectively 66,66%; 56,25%; and 72,72% which means that the existing conditions of the Trans Metro Deli bus have not been complied 100% based on the Minimum Service Standards PM 27 of 20115 (Standar Pelayanan Minimal PM 27 Tahun 2015). The results of the descriptive analysis study for the characteristics of passengers who use the Trans Metro Deli buses, based on gender which is 80% female, resides in Medan is 88%, are aged 15-25 years old is 78%, employment is 82% students, in-family roles as children is 90%, none ownership of vehicle is 49%, income < Rp500.000 is 49%, travel origination of house/boarding house/rent house is 61%, travel destination is 42% school/college, travel frequency 2 times per day is 53%, travel frequency 26-30 times per month is 38%, travel mode from the origin to the bus stop by walking is 37%, travel mode from the bus stop to the destination by walking is 52%, travel distance from the origin to the bus stop > 400 meter is 33%, travel distance from the bus stop to the destination > 400 meter is 37%, 15-30 minutes travel time by Trans Metro Deli bus is 37% , < 15 minutes travel time from the origin to the bus stop is 65%, < 15 minutes travel time from the bus stop to the destination is 33%, travel cost from the origin to the bus stop Rp2000 – 4000 is 45%, and travel cost from the bus stop to the destination Rp2000 – 4000 is 43%.